A probabilistic model for multi-contestant races - Gakis, K.; Pardalos, P.; Choi, C.-H.; Park, J.-H. (Athens Journal of Sport, 2016)
Predictions of sports games have been recognized as an important area of study for its economic significance. The majority of models for such games cover two - player games and the resulting championships or study individual players or teams and their resulting comparative position. However, many sports involve race-type multi-contestant games, which are more complex in modeling. In this paper we outline the difficulties associated with the study of such races